If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 8 = 0(x) Reorder the terms: 8 + X = 0(x) Anything times zero is zero. 8 + X = 0x Solving 8 + X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + X = 0 + -8 Combine like terms: 8 + -8 = 0 0 + X = 0 + -8 X = 0 + -8 Combine like terms: 0 + -8 = -8 X = -8 Simplifying X = -8
| (2X-1)(3X)=0 | | =7-4+3*0+1 | | t^2-6t+25=0 | | 0.8x-1.5=4.3x+1.9 | | (3X-2)(2X)=0 | | 5x+25=8x-2 | | n-7=-5+2n-1+2 | | (3x-2)(x+5)=14x-8 | | ln(4x)=61 | | 67=-98+5x | | 12y^2+7y+8= | | -10-6n=-52 | | (2x^2)-3x+3=0 | | 96=1.6x | | 7-2+x=5-2 | | 6t^2-24t+16=0 | | 13y=4x | | 3x-2+10= | | 3+3*6-2=x | | 0.3(x+40)-0.07(x-20)=8.8 | | -6(m-8)=-2m | | 13y=9x | | X+2x=30(x) | | -3n+7-2n=-13 | | 8x+8+3y=36 | | 5(y+3)-4(1-5y)=-39 | | 17=8x+1-4x | | 4y-4x^3=0 | | 18/-3=6 | | y=x^2+6x+14 | | 4x^2+16x-12y-44=0 | | 51=-3(m+7)+m |